Coccids – As Willow Pests (Coccinea) - A.T.Akhmedov; L.K.Yunusova (Zien Journals, 2022)
The article describes the flora of Uzbekistan. The richest flora of Central Asia has more than 6000 species of different plants. The richest in species in the flora of the republic are complex, legume cereals, marsh and others. The most common in the conditions of Uzbekistan are considered to be willow trees. Representatives of insects from the order Equidacteriaceae often cause serious harm. The author considers coccids as small insects with a stabbing-sucking oral apparatus that are harmful to willows.
Keywords: willow; trees; insects; Homoptera